Obtenção de uma desintegrina recombinante de Agkistrodon contortrix laticinctus e estudo dos efeitos de desintegrinas na expressão do fator de crescimento de endotélio vascular - Ribeiro, Juliana Uema (2005)
Disintegrins are snake venom proteins used in the study of integrin-mediated cellular adhesion through integrins. Recombinant disintegrin production may notable supply faster, larger and most homogeneous protein samples than bruit venom processing. This work describes optimization of the recombinant ACLD-C expression technique. ACLD-C is a disintegrin-like protein from Agkistrodon contortrix laticinctus, that have a disintegrin-like domain with DCD motif, and a cysteine-rich domain. This protein was subcloned from the ACLD clone (GenBank U86634), a metallopeptidase. A protocol of expression was established in our laboratory, where recombinant ACLD-C is produced in E. coli, using the expression vector pMal-p. This allows protein target expression in form of N-terminal fusion with MBP (maltose-binding protein), that facilitate purification, correct folding and production of disintegrin in soluble form. In fact, MBP/ACLD-C was was expressed in soluble form and purified in two stages: affinity comatography in amilose resin and cromatography of gel-filtration in superdex-200 resin. Modifications in expression protocol optimized MBP/ACLD-C expression in culture of 0,4 mg/L of culture of 1,2 mg/L (12,6% total of protein in periplasmic space of E.coli). MBP/ACLD-C imobilizated in amilose resin was subjected to digestion with enzyme factor Xa to separate ACLD-C of MBP. The separation was confirmed through positive reaction with anti-ALT-C antibody. ALT-C is a disintegrin-like protein from Bothrops alternatus. ALT-C induced both expression of VEGF in human fibroblasts and proliferation of endothelial cells and angiogenesis. In second part of this work, we investigated if MBP/ACLD-C was also able to induce the expression of this growth factor in this cells. MBP/ACLD-C and two other disintegrins, echistatina, a disintegrin-RGD, and EC6, a heterodimeric disintegrin, were incubated with fibroblasts. The influency of these proteins in VEGF expression was evaluated by ELISA. MBP/ACLD-C was able to strongly induce the expression of VEGF until 4 hours, when the level decreased until 24 hours. Experiment in period of 24 48 hours was not done due to problems of contaminations. Echistatin did not induced VEGF expression, but induced fibroblasts dettachment from plastic. The latter event was not observed in MBP/ACLD-C or EC6 incubated cells.